The Result of a Holy Alliance: Debus and Tariqah in Banten Province - Rohman Rohman (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
In this paper, the writer describes the practice of debus in Banten and its function among present-day Bantenese.The underlying question to be considered here is the way in which debus perfor-mances are now regarded as an integral part of Banten’s tradition. There is anumber of studies devoted to debus in Banten and in several places in Indonesia,most of which are anthropological studies. Little attention has been given to an in-depth study of debus practised by the Bantenese. In fact, debus has developedas invulnerability performance and has gone much further of late than the previous invulnerability performances in Aceh described by Snouck at the end of the nineteenth century. The writer attempts to show how the debus perfor-mances combined with aspects of tariqah’ now also include several new attributes